2005
DOI: 10.1136/jcp.2004.022129
|View full text |Cite
|
Sign up to set email alerts
|

Use of native or platelet count adjusted platelet rich plasma for platelet aggregation measurements

Abstract: Background: It is still not clear whether native or platelet count adjusted platelet rich plasma (PRP) should be used for platelet aggregation measurements. Aim: To evaluate the necessity of using adjusted PRP in platelet function testing. Methods: Platelet aggregation with native PRP and adjusted PRP (platelet count: 250/nl, obtained by diluting native PRP with platelet poor plasma) was performed on the Behring Coagulation Timer (BCTH) using ADP, collagen, and arachidonic acid as agonists. Healthy subjects, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 14 publications
1
47
0
1
Order By: Relevance
“…Recent studies demonstrated that platelet counts in PRP within the range that is observed in PRP samples from subjects with normal platelet count in whole blood do not affect the results of LTA studies [19][20][21][22]. Therefore, the common practice of adjusting the platelet count in PRP with autologous PPP is not recommended, because it is unnecessary and may impair the platelet responsiveness to agonists [21].…”
Section: Blood Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that platelet counts in PRP within the range that is observed in PRP samples from subjects with normal platelet count in whole blood do not affect the results of LTA studies [19][20][21][22]. Therefore, the common practice of adjusting the platelet count in PRP with autologous PPP is not recommended, because it is unnecessary and may impair the platelet responsiveness to agonists [21].…”
Section: Blood Collectionmentioning
confidence: 99%
“…After review of the full manuscripts by the panel members, fifteen further studies were excluded. These 12 manuscripts, coupled with two extra studies identified by manual review and by consultation among members of the working group, resulted in a total of only 14 relevant studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30] that were used to help refine the RAND survey and write the present recommendations ( Fig. 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this practice could also affect platelet function independently of the induced change in platelet count, as PPP may contain substances affecting platelet function that are released by platelets or other blood cells during high-speed centrifugation of blood samples necessary to obtain PPP. 5 This study examines whether or not dilution of PRP with autologous PPP also affects the results of platelet aggregation studies independently of the induced decrease in platelet count.…”
mentioning
confidence: 99%
“…The platelet count is not reported, and by implication the results were not corrected for the possible influence of the well described reactive thrombocytosis that is associated with disease activity in PsA, although previous work has shown that platelet count does not significantly influence platelet aggregation measurements 10 . Also, the platelet function assays that were used assessed the platelet responses, separately, to each of only 2 concentrations of arachidonic acid and a single concentration of ADP, the concentrations tested were in the low submaximal range, and the clinical applicability of such an approach has been called into question 11 .…”
mentioning
confidence: 99%